Northward expansion of the westerlies over glacial southeastern Australia: evidence from semi-arid lunette dunes, temperate basalt plains, and wind modelling - Fitzsimmons, Kathryn E.; Gromov, Sergey S. (Frontiers in Earth Science, 2022)
It has long been hypothesized that the last glacial maximum (LGM) oversaw cold, arid, windy climates across southern Australia, and that these were driven by intensification and northward expansion of mid-latitude westerly circulation. Moreover, it was recently suggested that Australia experienced an extended LGM which began several millennia before the global peak. Aeolian sedimentary deposits provide key evidence for these hypotheses, and climate modelling an alternative means to test them. As yet, however, combined approaches to reconstructing glacial environments on the continent are scarce. Here we provide new evidence for westerly wind regimes across glacial southeastern Australia. We confirm active transverse lunette deposition at c. 29 ka and c. 23-19 ka in the semi-arid Willandra Lakes, and identify aeolian sand incursions to Spring Creek on the temperate Western Victorian Volcanic Plains from c. 29 ka. The Spring Creek deposits contain a surprising quantity of sand-sized quartz given the basalt setting, which we propose to be allochthonous and likely transported some distance. The site lies more than 50 km east and south of dunefields which were active at the same time and may have contributed sediment via long distance transport. We investigate the hypothesis for northward glacial expansion of westerly winds by combining our sediment records with aeolian particle transport simulations. We find that LGM near-surface winds were dominated by stronger, more focussed westerly air flow across southeastern Australia, compared with presently more diffuse wind regimes. Our results suggest stronger potential for LGM eastward distal sand transport onto the basalt plains, coeval with enhanced aeolian activity in the semi-arid Australian dunefields. Our combined reconstruction of aeolian deposition and trajectory modelling confirms the extended LGM hypothesis and indicates a northward migration of westerly winds over southeastern Australia during this period.